Snow and Dickens: The Victorian ‘Inconvenient Truth’ - Wayne Melville et Philip V. Allingham (Cahiers Victoriens et Edouardiens)
Scientists’ investigations into environmental issues often fail to promote political change unless those investigations are popularised in the public consciousness. We will illustrate this thesis through the work of Dickens and the pioneering physician, Dr John Snow. In Victorian London, Snow challenged the deeply held theory that miasmas caused diseases such as cholera. However, his investigations, now considered the foundation of modern epidemiology, were dismissed by the medical establishment. By 1884, his work had been verified. Contemporaneously, Dickens worked with early advocates of public health, Edwin Chadwick and his brother-in-law, Henry Austin, to promote and then defend the landmark 1848 Public Health Act. By 1850, however, the Public Health Act was being eviscerated, and Dickens attacked the vested interests he saw as opposed to public health. Fast forward to the present, and we see this history repeating itself in the issue of global warming. The science of global warming has been developing since the 1820s and is now well accepted, but serious political debates continue in North America over scientific uncertainty and the economic costs of tackling the problem.